Improving yields by switching central metal ions in porphyrazine-catalyzed oxidation of glucose into value-added organic acids with SnO2 in aqueous solution - Zhang, Quanquan; Li, Xin; Wang, Xingwang; Huang, Xin; Liu, Yuncai; Wu, Fengshou; Zhang, Bingguang; Deng, Kejian (Frontiers in Chemistry, 2023)
Photocatalysis has exhibited huge potential in selective conversion of glucose into value-added chemicals. Therefore, modulation of photocatalytic material for selective upgrading of glucose is significant. Here, we have investigated the insertion of different central metal ions, Fe, Co, Mn, and Zn, into porphyrazine loading with SnO2 for access to more efficient transformation of glucose into value-added organic acids in aqueous solution at mild reaction conditions. The best selectivity for organic acids containing glucaric acid, gluconic acid, and formic acid of 85.9% at 41.2% glucose conversion was attained by using the SnO2/CoPz composite after reacting for 3 h. The effects of central metal ions on surficial potential and related possible factors have been studied. Experimental results showed that the introduction of metalloporphyrazine with different central metal ions on the surface of SnO2 has a significant effect on the separation of photogenerated charges, changing the adsorption and desorption of glucose and products on the catalyst surface. The central metal ions of cobalt and iron contributed more to the positive effects toward enhancing conversion of glucose and yields of products, and manganese and zinc contributed more to the negative effects, resulting in the poor yield of products. The differences from the central metals may attribute to the surficial potential change of the composite and the coordination effects between the metal and oxygen atom. An appropriate surficial potential environment of the photocatalyst may achieve a better interactive relationship between the catalyst and reactant, while appropriate ability of producing active species matched with adsorption and desorption abilities would gain a better yield of products. These results have provided valued ideas for designing more efficient photocatalysts in selective oxidation of glucose utilizing clean solar energy in the future.